Interações entre beija-flores (aves: trochilidae) e plantas em ambientes florestais da mata atlântica - Lins, Mariane Souza (2023)
Among nectarivorous birds, hummingbirds are the most specialized in plant pollination. Climate seasonality, flowering and the different stages of vegetation succession influence the availability of resources in time and space for hummingbirds and, consequently, the structure of interactions between hummingbirds and plants. Our aim was to investigate the assembly of hummingbirds and their mutualistic interactions with the plants they pollinate, under the effect of seasonality and resource availability, in two successional stages of vegetation (advanced - A1 and intermediate - A2 regeneration) of the Atlantic Rainforest, Alagoinhas, Bahia, Brazil. This study was carried out between October 2021 and November 2022, where hummingbirds and plants were recorded, considering functional attributes that influence pollination. Based on this information, networks of mutualistic interactions between hummingbirds and pollinating plants were developed in the two successional stages of the vegetation. We recorded ten species of hummingbirds and fifteen species of angiosperms that were visited by hummingbirds, thirteen species in A1, five of which were ornithophiles, and six species in A2, one of which was ornithophile. Bowdichia virgilioides (Kunth) and Vochysia thyrsoidea (Klotzsch ex M.R. Schomb.) were the non-ornithophilous species most used by hummingbirds in both areas. The most representative family in terms of number of species visited was Bromeliaceae (4 spp). Flowering was annual, with a low density of flowering in some months of the year, mainly in A2; the majority had an intermediate duration and intense flowering. The network of interactions in the two successional stages of vegetation showed a modular structure with low nesting: in A1, the size of the network was 1,280 interactions, with a richness of 23 species that made up the network, with 31.5% connectivity and in A2, the size of the network was 263 interactions, with a richness of 12 species that made up the network, with 41.5% connectivity. The hummingbirds that had the highest degree of interactions with the plants in A1 were Chrysolampis mosquitus, Eupetomena macroura and Phaethornis ruber and, among the plants with the highest degree of hummingbird visits, Ananas bracteatus, Pyrostegia venusta, Odontadenia lutea and Hohenbergia stellata; in A2, Chrysolampis mosquitus and Phaethornis ruber among the trochilids, and Vriesea procera, Lafoensia pacari and Vochysia lucida among the plants. Climate seasonality, flowering and successional stages shaped the structure of the interaction networks, allowing us to understand how these interferences influence the hummingbird-plant relationship and how these interactions are fundamental to the maintenance of these assemblages in different successional stages of vegetation.